Resource-Efficient Fault-Tolerant Quantum Computing Architectures Based on Surface Codes with Dynamic Error Suppression - Rith, Vicheka; Kiri, Ming; Idris, Adam (Journal of Tecnologia Quantica, 2025)
Quantum computing has the potential to revolutionize industries by solving complex problems that are intractable for classical computers. However, achieving fault tolerance in large-scale quantum systems remains a significant challenge due to the high resource overhead required for error correction. Surface codes, a leading quantum error correction technique, provide robust fault tolerance but demand a large number of physical qubits. This research explores a resource-efficient approach by integrating dynamic error suppression with surface codes to reduce qubit overhead while maintaining fault tolerance in quantum computing architectures. The objective of this study is to investigate how dynamic error suppression can enhance the performance of surface code-based quantum computing architectures by minimizing resource usage and improving system reliability. The research employs computational simulations to model quantum systems under varying error rates, qubit numbers, and dynamic error correction strategies. The results demonstrate that combining dynamic error suppression with surface codes significantly reduces the physical qubit overhead while maintaining or improving fault tolerance. The proposed architecture achieves higher efficiency and robustness in large-scale systems, especially at higher error rates. In conclusion, this study offers a practical solution for scaling quantum computing systems by optimizing resource usage without compromising fault tolerance. These findings have important implications for the development of efficient, fault-tolerant quantum computers suitable for real-world applications.